Identification of genes transcriptionally responsive to the loss of MLL fusions in MLL-rearranged acute lymphoblastic leukemia. - Marieke H van der Linden (PLoS ONE, 2015)
MLL-rearranged acute lymphoblastic leukemia (ALL) in infants (<1 year) is characterized by high relapse rates and a dismal prognosis. To facilitate the discovery of novel therapeutic targets, we here searched for genes directly influenced by the repression of various MLL fusions.For this, we performed gene expression profiling after siRNA-mediated repression of MLL-AF4, MLL-ENL, and AF4-MLL in MLL-rearranged ALL cell line models. The obtained results were compared with various already established gene signatures including those consisting of known MLL-AF4 target genes, or those associated with primary MLL-rearranged infant ALL samples.Genes that were down-regulated in response to the repression of MLL-AF4 and MLL-ENL appeared characteristically expressed in primary MLL-rearranged infant ALL samples, and often represented known MLL-AF4 targets genes. Genes that were up-regulated in response to the repression of MLL-AF4 and MLL-ENL often represented genes typically silenced by promoter hypermethylation in MLL-rearranged infant ALL. Genes that were affected in response to the repression of AF4-MLL showed significant enrichment in gene expression profiles associated with AF4-MLL expressing t(4;11)+ infant ALL patient samples.We conclude that the here identified genes readily responsive to the loss of MLL fusion expression potentially represent attractive therapeutic targets and may provide additional insights in MLL-rearranged acute leukemias.